Analisis Senyawa Bioaktif Daun Tempuyung (Sonchus arvensis L.) sebagai Kandidat Obat Herbal Antibatu Ginjal - Yulisma, Ardhana; Ilda Rosa Yuliana (Jurnal Serambi Engineering, 2026)
Nephrolithiasis, otherwise known as kidney stones, is a serious condition that is becoming increasingly prevalent, particularly in developing countries such as Indonesia. This increase in cases can be attributed to a combination of unhealthy lifestyles and genetic factors. Despite the efficacy of conservative therapy for nephrolithiasis, its side effects have led to the need for alternative treatments based on natural ingredients. The objective of this study was to analyze the active compounds present in tempuyung leaves and to evaluate their potential as a herbal remedy for kidney stones. The experimental laboratory techniques employed included extraction, phytochemical testing, quantitative analysis, and data analysis. The results of the study on the tempuyung leaf extract demonstrated the presence of bioactive compounds, including flavonoids, alkaloids, saponins, tannins, and triterpenoids, which have the potential to serve as anti-kidney stone agents. Subsequent HPLC/LC-MS analysis of the flavonoid compound group revealed that certain compounds, including quercetin, luteolin, apigenin, rutin, and kaempferol, possess anti-inflammatory, nephroprotective, antioxidant, and kidney stone dissolution properties. Consequently, tempuyung can be posited as a potential candidate for consideration in the development of phytopharmaceuticals for the treatment of kidney stones.